Semen collection in male dogs by means a vibrator - ΚΟΥΤΣΟΥΡΗΣ Χ. (Journal of the Hellenic Veterinary Medical Society, 2019)
A new technic of collecting semen from dogs by means of a dry battery working vibrator, is described. The semen is collected in a semen cup. The ejaculation is induced by placing the vibrating cup on to the penis’s glans. Ejaculation was succeded only in 50% of the dogs and only small quantity of semen was obtained. Because of this the apparatus can be used only for qualitative examination of semen but not to obtain semen for artificial insemination. The probable causes of the small percentage of the ejaculated dogs as well as the reason for obtaining a small volume of semen, are discussed